Synthesis and Characterization of Biochar-Based Geopolymer Materials - Federica Piccolo; Fernanda Andreola; Luisa Barbieri; Isabella Lancellotti (Applied Sciences, 2021)
The aim of this research is to evaluate the possibility to realize alkali-activated materials exploiting biochar, a secondary raw material coming from pyrolysis/gasification processes, for environmental benefits, such as improvement of soil fertility and reduction of CO2 emissions into the atmosphere thanks to the carbon sink process where carbon dioxide is subtracted from the cycle of carbon. For the matrix of the geopolymers, a waste material derived from incinerator bottom ash was used and compared to pure metakaolin matrix. The materials obtained are lightweight and porous, with high water absorption capacity and moisture adsorption/desorption. BET analysis shows an increase in specific surface by increasing the biochar content and the biochar acts as a filler in the pores. From porosimetry analysis it is possible to follow the evolution of the curing process of the geopolymer prepared: specimens containing 70 wt% biochar after 28 and 90 days showed an increase in total Hg intrusion volume, pore area and total porosity but a decrease in the dimensions of pores. Due to the technical properties of materials containing biochar, they can be used in the future for a cleaner design of products in the field of sustainable construction for insulating panels or lightweight materials for houses and gardens in terraces and balconies.